Pre-tactical time window assignment: Runway utilization and the impact of uncertainties - Heidt, Andreas; Kapolke, Manu; Liers-Bergmann, Frauke; Fürstenau, Norbert; Helmke, Hartmut (SIDs 2014 - Proceedings of the SESAR Innovation Days, 2014)
Efficient planning of runway utilization is one of the main challenges in Air Traffic Management (ATM). It is important because runway is the combining element between airside and groundside. Furthermore, it is a bottleneck in many cases. In this paper, we develop a specific optimization approach for the pre-tactical planning phase that reduces complexity by omitting unnecessary information. Instead of determining arrival/departure times to the minute in this phase yet, we assign several aircraft to the same time window of a given size. The exact orders within those time windows can be decided later in tactical planning. Mathematically, we solve a generalized assignment problem on a bipartite graph. To know how many aircraft can be assigned to one time window, we consider distance requirements for consecutive aircraft types. We develop an optimization model, which can be solved fast in practice but may provide unnecessary large time buffers, and extend it to a model that solves the problem to global optimality. In reality, uncertainty and inaccuracy almost always lead to deviations from the actual plan or schedule. We present computational results concerning the abovementioned optimization approaches and investigate the impact of disturbances on our deterministic solutions. As a next step, we will incorporate uncertainties directly in our model. Therefore, we analyze real-world data from a large German airport in order to obtain realistic delay distributions and describe a simulation environment to test current and future solution methods.
CRIS-Team Scopus Importer:2023-03-07